The COVID-19 pandemic and the public health challenges in Bangladesh: a commentary - Amlan Haque (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The purpose of this paper is to highlight the current pandemic situation of coronavirus disease 2019 (COVID-19) in Bangladesh, how the Government is managing this unprecedented condition and encountering these increasing public health challenges. Design/methodology/approach - This paper is a viewpoint of the current COVID-19 pandemic situation in Bangladesh. Findings - As one of the most densely populated countries, Bangladesh is vulnerable to COVID-19. Currently, the infection of COVID-19 is spreading fast and started to capture all the parts of Bangladesh. The Government of Bangladesh has already taken several preventive measures to overcome the pandemic such as declaring hotspots of COVID-19 and setting lockdowns, increasing mass awareness through social media and satellite TV channels. They are also encouraging private and community healthcare initiatives to increase hospital beds and COVID-19 treatment facilities. Besides, the Government has deployed defence force and additional health workers and increased public holidays to reduce the number of coronavirus infections. However, both the number of infected people and the death toll is rising, and there are growing challenges that the Government and public healthcare professions need to overcome. Originality/value - This paper delivers information about the present developing situation of COVID-19 in Bangladesh, how the Government is handling and public health challenges that have raised. This paper can be helpful for the policymakers and Government officials for effective public health interventions.